Adaptação transcultural, evidências de validade da escala yuth outcome questionnaire 2.01 para o português brasileiro e sua aplicabilidade clínica na área da psicoterapia com crianças e adolescentes - Holst, Bruna (2019)
Evidences of validity of the Youth Outcome Questionnaire – Y-OQ 2.01, parents and legal guardians version, to Brazilian Portuguese. Introduction: Clinical interventions in childhood and adolescence are essential for the promotion of mental health and quality of life, as well as for the prevention of severe disorders in adulthood. Psychotherapy is the process that, through interpersonal influence and psychological processes such as learning, persuasion and social support, aims to promote mental health, cope with conflicts, and decrease behavioral problems and mental disorders. Instruments that present evidence of validity are important tools in assessing outcome and process in psychotherapy, and are essential to support evidence-based psychotherapy. The Youth Outcome Questionnaire 2.01 (Y-OQ 2.01) was developed to meet the demand for evaluation of psychotherapy with children and adolescents. It is a brief tool, sensitive to change and meets rigorous psychometric standards of validity and reliability. It is selfadministered and consists of 64 items, answered by parents or legal guardians of children or adolescents, on a Likert scale ranging from 1 to 5. Objective: Investigate evidence of validity of the Y-OQ 2.01 for use in the Brazilian Portuguese language. Method: This thesis consists of three papers, one theoretical and two empirical. The theoretical paper presents a systematic review that investigated prevailing research designs and instruments used in Brazilian studies with psychotherapeutic interventions with children and adolescents. The first empirical article describes the transcultural adaptation and the investigation of the Y-OQ 2.01 psychometric properties, more specifically evidences of content validity and construct validity, through exploratory factorial analysis and network analysis. The second empirical article aims to investigate social determinants associated with the development of psychological and behavioral problems in children and adolescents. 341 parents or legal guardians of children (N=172) and adolescents (N=163) from 1 to 19 years old (M=9.44; SD=4.20) participated in the study. The Y-OQ 2.01 and a social-demographic data questionnaire were applied. Results: The systematic review pointed to a gap of studies (N=28, without temporal limitation) in the area of psychotherapy with children and adolescents in the Brazilian context, especially studies that evaluate the interventions’ results through instruments that present evidence of validity. Among the studies that used some type of measurement, it was observed the poor detailing regarding validity and reliability information. Based on the identification of the demand for instruments that present evidence of validity for the Brazilian context for the evaluation of the process and result of psychotherapy with this age group, the Y-OQ 2.01 was chosen for a cross-cultural adaptation and investigation of evidence of validity – process described in the first empirical study. The results demonstrated evidence of content and construct validity for the Y-OQ 2.01 Brazilian Portuguese version, and a two-factor structure (internalizing and externalizing) for this population. Cronbach’s alphas for both factors were 0.92 and 0.93, respectively. The second empirical study pointed out that girls tend to manifest more internalizing symptoms, while boys demonstrate externalizing behaviors and symptoms. It was identified in this study that gender, age group, parents’ marital status and ethnicity/skin colour/race reported can act as risk factors for psychological and behavioral problems, and the Y-OQ 2.01 was sensitive to differentiate clinical and non-clinical populations. Conclusion: The Y-OQ 2.01 showed evidences for its use as a tool for planning, monitoring and evaluation of results of psychotherapeutic treatments by clinicians of different theoretical approaches in Brazil. In addition, the study also made it possible to reflect on symptoms and treatments of children and adolescents in the Clinical Psychology area.